2005
DOI: 10.1136/jcp.2004.022830
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium bacteraemia characterised by 16S ribosomal RNA gene sequencing

Abstract: Background: Owing to problems in accurate species identification of the diverse genus clostridium, the epidemiology and pathogenicity of many species are not fully understood. Moreover, previous studies on clostridium bacteraemia have been limited and relied only on phenotypic species identification. Aims: To characterise the epidemiology, disease spectrum, and outcome of clostridium bacteraemia using 16S ribosomal RNA (rRNA) gene sequencing. Method: During a four year period (1998)(1999)(2000)(2001), all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…In this study, we focused on Clostridium perfringens to determine its copresence with C. difficile because it is a common clinically diagnosed bacterial pathogen that causes diarrhea. In addition, 16S rRNA gene sequencing is capable of identifying C. perfringens at the species level (33). Considering the difficulty of detecting low-abundance organisms using the metagenomic approach, the presence of C. perfringens was designated only when the organism was identified by both the 16S rRNA gene approach and MSS.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we focused on Clostridium perfringens to determine its copresence with C. difficile because it is a common clinically diagnosed bacterial pathogen that causes diarrhea. In addition, 16S rRNA gene sequencing is capable of identifying C. perfringens at the species level (33). Considering the difficulty of detecting low-abundance organisms using the metagenomic approach, the presence of C. perfringens was designated only when the organism was identified by both the 16S rRNA gene approach and MSS.…”
Section: Resultsmentioning
confidence: 99%
“…Application of the technique has led to recognition of many previously undescribed or 'rarely encountered' anaerobic Gram-positive rods for their associations with more serious diseases than previously thought (Bosshard, Zbinden, & Altwegg, 2002;Chan, Lau, et al, 2012;Lau, McNabb, et al, 2007;Woo, Lau, Chan, et al, 2005;. We have previously used 16S rRNA gene sequencing to characterise bacteraemia caused by anaerobic, non-sporulating, Gram-positive rod and found that the former genus Eggerthella accounted for a high proportion of clinically significant bacteraemia .…”
Section: Defining Disease Associations and Epidemiologymentioning
confidence: 96%
“…The unique colony morphology of C clostridioforme and its appearance as fusiform or boat-shaped rods that may appear as Gram-stainingvariable should aid in its identification. In susceptibility tests, the use of 10 mg vancomycin per disc would show that the organism is susceptible to vancomycin and therefore not likely to be Gram-negative; however, 16S rRNA gene sequencing may be required for accurate identification (Woo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%